Membranes, molecules and biophysics: enhancing monocyte derived dendritic cell (MDDC) immunogenicity for improved anti-cancer therapy - Rauch, Cyril; Ibrahim, Hiba; Foster, Neil (Herbert Publications, 2013)
Despite great medical advancement in the treatment of cancer, cancer remains a disease of global significance. Chemotherapeutics can be very expensive and drain medical resources at a national level and in some cases the cost of treatment is so great that it prohibits their use by local health authorities. Drug resistance is also a major limiting factor to the successful treatment of cancer with many patients initially responding well but then becoming refractory to treatment with the same drug and in some case may become multi-drug resistant. The immune system is known to be important in the prevention of tumors by eliminating pre-cancerous or cancerous cells. This concept of immune surveillance has largely been super-ceded by the concept of immunoediting whereby the immune system imposes a selective pressure on tumor cells which may either control tumor growth or inadvertently select for tumor cells which have evolved to escape the immune response and which may induce tumor development. Stimulation of the immune system by vaccination offers many benefits in the treatment of cancer. It is highly cost effective and vaccines can be manipulated to include multi-antigens which in some cases may overcome equilibrium (and selective pressure) while also preventing the establishment of reactivated cancer cells, since cancer antigen-specific memory would be induced following the initial vaccination/booster phase. To date studies using vaccination as a treatment for cancer have been a little disappointing, probably due to insufficient level of immunogenicity. In this review we will discuss methods of manipulation of the immune system to increase the anti-cancer activity of dendritic cells in vivo and how monocyte derived dendritic cells may be manipulated ex vivo to provide more robust, patient-specific treatments.